NF / CoFeS-CoP-FeP composite material with three-phase heterostructure as well as preparation method and application of NF / CoFeS-CoP-FeP composite material
By loading binary transition metal elements on the surface of foam nickel NF and sulfidizing and phosphating, a three-phase heterostructure is constructed, which solves the problems of low catalyst activity and poor stability in the prior art, and achieves efficient electrocatalytic hydrogen evolution performance and good cycle stability.
Patent Information
- Application Number
- CN202411687805.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The prior art is difficult to construct a three-phase heterostructure, resulting in fewer active ingredients, lower intrinsic catalytic activity, and poor structural stability.
By loading binary transition metal elements on the surface of nickel foam NF and controlling the amount of sulfur, partial vulcanization is achieved, and the unsulcanized transition metal is phosphated, thereby building a three-phase heterostructure.
Through multi-component synergistic action, the catalyst's adsorption ability to hydrogen atoms is achieved, the charge transfer resistance is reduced, the electrocatalytic hydrogen evolution performance is improved, and the catalyst's stability and cycling performance are improved.
Smart Images

Figure CN119506960A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic hydrogen evolution, and in particular to a NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, and a preparation method and application thereof. Background Art
[0002] Platinum-based precious metal materials have low overpotential, large exchange current density and good stability, and are currently the most attractive HER electrocatalysts. However, the scarcity and high price of precious metals limit the commercial application of such materials. There are also problems such as susceptibility to corrosion and reduced life under strong acid or strong base conditions. Therefore, the current common solution is to use low-cost non-precious metal HER electrocatalysts, such as transition metal sulfides, which have been widely used as alkaline water electrolysis hydrogen evolution materials. Among them, the S atoms in single-component transition metal sulfides usually regulate the electronic configuration of transition metals by generating S vacancies to promote the dissociation of water molecules, and have good HER performance. However, single-component transition metal sulfides as hydrogen evolution reaction catalysts have problems such as fewer active components and low intrinsic catalytic activity.
[0003] In order to solve the problem of poor catalytic performance of single-component transition metal catalysts due to low intrinsic activity of the catalyst, the synergistic enhancement effect can be achieved at different active sites and electronic reconstruction interfaces through the synergistic effect of multiple components, so as to improve the catalyst's adsorption capacity for hydrogen atoms and promote the electrochemical hydrogen evolution reaction. For example, the existing document 1 (Ni-Mo-STernary Chalcogenide Thin Film for Enhanced Hydrogen Evolution Reaction [J]. Catalysis Letters, 2021.) uses a two-step method of co-sputtering and thermal sulfurization of Ni-Mo alloy films to prepare Ni-Mo-S ternary sulfide films with different Ni concentrations. The Ni-Mo-S film obtained by this technical solution has a Ni concentration of 50 at.%, at a current density of 10 mA cm -2 Under the condition of , the overpotential is 400mV. The reason is that the introduction of Ni element can change the morphology and electronic structure of MoS2 film, thereby promoting HER kinetics, and can improve the adsorption of H ions, thereby improving the performance of electrocatalytic hydrogen evolution reaction. However, since the basic morphology of the material obtained by this technical solution is a thin film, it directly leads to a small double-layer capacitance value caused by the planar two-dimensional structure, as well as the instability of the structure itself, which is specifically reflected in the obvious attenuation of the potential when the number of CV cycles is 1000 times.
[0004] In order to solve the problems of small electrochemical active surface area and poor structural stability of multi-transition metals, the catalyst morphology can be regulated by anion synergistic doping, the electrochemical active surface area can be increased, and the HER performance can be improved. Among them, the introduction of the P element can form a synergistic effect through the S element and the P element, which can promote the adsorption of thermoneutral electrons and realize electron redistribution, thereby increasing the electrochemical active area, and realizing activation when adsorbing hydrogen ions, that is, obtaining activated hydrogen ions, thereby reducing the energy barrier of the hydrogen evolution reaction and accelerating the hydrogen evolution reaction rate. For example, the existing document 2 (Facile hydrothermal synthesis of combined MoSe2PS nanostructures on nickel foam with superior electrocatalytic properties for hydrogen evolution reaction [J]. International Journal of Hydrogen Energy, 2023.) synthesized a MoSe2PS composite nanomaterial with a petal structure covered with slender nanoleaves on the surface of nickel foam by a three-step hydrothermal method. This technical solution has achieved a high performance at 10 mA cm -2 The overpotential reaches 90mV at a current density of 1.38kV. The reason is as mentioned above, because the P and S elements effectively increase the electrochemical active sites of MoSe2, and improve the adsorption and desorption of hydrogen atoms on the catalyst surface. However, this structural morphology also leads to new technical problems, that is, the petal-shaped MoSe2PS composite nanomaterial covered with slender nanoblades is in direct contact with the electrolyte during the hydrogen evolution reaction, and the catalyst partially falls off after a long cycle, resulting in poor stability of the technical solution.
[0005] In order to improve the stability of multi-transition metal catalysts, the stability of the composite material can be improved by constructing a heterostructure and through the strong coupling of heterogeneous interfaces. Existing literature 3 (High activity and stabilityin Ni2P(Co,Ni)OOH heterointerface with a multiple-hierarchy structure foralkaline hydrogen evolution reaction[J].Nano Research,2023.) First, nickel foam is used as the working electrode, Hg / HgO as the reference electrode, and graphite rod as the counter electrode. Cobalt chloride hexahydrate aqueous solution is used as the electrolyte to obtain (Co,Ni)OOH by electrodeposition, and then phosphorus powder is used as the raw material to obtain Ni2P(Co,Ni)OOH by annealing. This technical solution has achieved a current density of 100mA·cm-2 Under the condition of , the overpotential is only 169mV, and the current decay is negligible after 36h of chronopotentiometry. The reason for the improved performance of this technical solution is that the strong charge transfer at the Ni2P(Co,Ni)OOH heterogeneous interface eliminates the spin asymmetry to achieve the thermoneutral adsorption of active H atoms, and the resulting Coulomb attraction firmly stacks the two materials together, while improving the stability and hydrogen evolution catalytic performance.
[0006] In order to improve the performance of electrocatalytic hydrogen evolution, a third phase component can also be introduced. For example, the previous work results of the research group of the inventor of the present invention, the existing document 4 (NF / rGO / CoNi2S4-MoO2 nanosheets with a core-shell structure formed: An efficient electrocatalyst for the hydrogen evolution reaction [J]. Journal of Alloys and Compounds, 2024, that is, application number: 2024110685776, a NFrGOCo-Ni-SMo-O self-supporting composite material and its preparation method and application) is based on nickel foam, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, urea and ammonium fluoride as raw materials, and reduced graphene oxide is introduced as a third phase component. The specific preparation method is to prepare NF / rGO / CoNi2O4 by hydrothermal method, and then use ammonium molybdate tetrahydrate and thiourea as raw materials to hydrothermally prepare NF / rGO / CoNi2S4-MoO2 again. The hydrogen evolution catalytic performance is achieved at a current density of 10mA cm -2 Under the condition of , the overpotential is only 65mV. The purpose of this technical solution is to simplify the preparation process and reduce the loss of active substances. Therefore, the purpose of selecting the third phase component as rGO, that is, its role in the technical solution is to use the active sites and adjustable micromorphology of rGO itself to composite with the self-supporting material NF with a smooth surface to anchor the active substance on the surface of NF and reduce agglomeration. Therefore, rGO does not form a three-phase heterogeneous structure with the other two components. This technical solution shows that not any preparation method can construct a three-phase heterogeneous structure by combining any three-phase components.
[0007] Therefore, the technical problem existing in the prior art is that, although a three-phase component or even a multi-phase component can be formed by introducing multiple transition metal cations or introducing sulfur and phosphorus anions, a three-phase heterogeneous structure cannot be constructed. Summary of the invention
[0008] The purpose of the present invention is to provide a NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure and a preparation method and application thereof.
[0009] The basic principle involved in the present invention is that in a heterogeneous structure, the strong coupling effect between the interfaces of the heterogeneous interfaces can enhance the binding force between the materials, accelerate the rapid transfer of electrons and ions in the entire electrocatalyst, and improve the cyclic stability and hydrogen evolution efficiency of the catalyst. In order to obtain the above-mentioned effect, the technical problem that the present invention actually solves is to construct a three-phase heterogeneous structure by a simple two-step method. The specific method is that when the binary transition metal element is loaded on the surface of the nickel foam NF, the amount of sulfur element added is controlled to achieve partial sulfurization, and then the unsulfurized transition metal is phosphated to construct a three-phase heterogeneous structure.
[0010] Among them, binary transition metal elements promote HER kinetics by changing the electron distribution through the interaction between different metals, thereby improving the adsorption of H ions, reducing the charge transfer resistance, and improving the performance of electrocatalytic hydrogen evolution.
[0011] The sulfides and phosphides formed after sulfidation and phosphidation promote the adsorption of thermoneutral electrons / ions through the synergistic effect of sulfur and phosphorus, realize the redistribution of electrons, increase the electrochemical active area, and obtain activation when adsorbing hydrogen ions, that is, obtain activated hydrogen ions, thereby reducing the energy barrier of hydrogen evolution reaction and promoting the performance of hydrogen evolution reaction;
[0012] The present invention can be simply summarized as follows: by performing phosphating on the basis of partially sulfided cobalt iron hydroxide, a three-phase heterojunction structure is constructed while obtaining a dual-doping synergistic effect, that is, through a simple preparation process, the microscopic morphology of the composite material is regulated and the hydrogen evolution performance and cycle performance of the catalyst are improved.
[0013] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:
[0014] A NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, using nickel foam as a substrate and a self-supporting skeleton, using cobalt nitrate hexahydrate and iron nitrate nonahydrate as raw materials, and using thiourea as a sulfur source, a partially sulfided cobalt iron sulfide and cobalt iron hydroxide NF / CoFeS-CoOH-FeOH are grown on the nickel foam by a hydrothermal method, and then sodium hypophosphite is used as a phosphorus source, and a one-step phosphating method is used to convert the cobalt iron hydroxide into cobalt iron phosphide, so that cobalt iron sulfide and cobalt iron phosphide NF / CoFeS-CoP-FeP grown on the nickel foam can be obtained;
[0015] The microstructure of the Co8FeS8 is a spherical Rubik's cube structure; the microstructure of the Co2P is a spherical nanosheet structure; the microstructure of the Fe2P is a nanosheet structure; and the spherical Rubik's cube-shaped Co8FeS8 and the spherical nanosheet-shaped Co2P are combined together and grown on the Fe2P nanosheets to form a three-phase heterostructure.
[0016] A method for preparing a NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure comprises the following steps:
[0017] Step 1, preparation of NF / CoFeS-CoOH-FeOH, first, cobalt nitrate hexahydrate, iron nitrate nonahydrate and thiourea are dissolved in deionized water to obtain solution A, solution A is stirred under certain conditions, then, under certain conditions, nickel foam NF is immersed in solution A for hydrothermal reaction, finally, after washing and drying, nickel foam simultaneously loaded with cobalt iron sulfide and cobalt iron hydroxide can be obtained, referred to as NF / CoFeS-CoOH-FeOH;
[0018] In the step 1, the mass ratio of cobalt nitrate hexahydrate, ferric nitrate nonahydrate and thiourea is 2:3:2;
[0019] In the step 1, the stirring condition of solution A is that the stirring time is 0.5-1h;
[0020] In the step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 160° C., and the hydrothermal time is 5 h;
[0021] In the step 1, the NF needs to be washed before immersion, and the washing method is to wash the NF with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence, and after washing, dry it at a drying temperature of 60°C;
[0022] Step 2, preparation of NF / CoFeS-CoP-FeP, first, sodium hypophosphite is placed upstream of the tube furnace, and NF / CoFeS-CoOH-FeOH obtained in step 1 is placed downstream of the tube furnace, and then calcined and phosphated under certain conditions. After the phosphating is completed, the obtained product is cooled, washed and dried to obtain a nickel foam simultaneously loaded with cobalt iron sulfide and cobalt iron phosphide, referred to as NF / CoFeS-CoP-FeP;
[0023] In the step 2, the mass ratio of sodium hypophosphite to cobalt nitrate hexahydrate in step 1 is 17:5;
[0024] In step 2, the calcination and phosphating conditions are: in an argon atmosphere, at a heating rate of 1°C min -1 , the calcination temperature is 300℃, and the calcination time is 1h.
[0025] A NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure is used as a hydrogen evolution catalyst material. When the current density is 10 mA cm-1 in a 1 M KOH solution, the -2 When NF / CoFeS-CoP-FeP is used, the overpotential is 61-67 mV, and the Tafel slope is 99.51-105.23 mV·dec -1 ; In 1M KOH solution, in the range of 0 to -0.1V, when the current density is 10mA·cm -2 When the cycle time is 24h, the current retention rate of NF / CoFeS-CoP-FeP is 98%.
[0026] The technical effects of the present invention have been tested and the specific contents are as follows:
[0027] The XRD test of the present invention shows that NF / Co-Fe-S / Co-P / Fe-P simultaneously has characteristic peaks of Co8FeS8, Co2P and Fe2P. Comparing the test results with step 1, it can be seen that step 2 successfully prepares Co2P and Fe2P, that is, NF / Co-Fe-S / Co-P / Fe-P is successfully prepared.
[0028] TEM and EDS tests show that the NF / Co-Fe-S / Co-P / Fe-P of the present invention successfully synthesizes uniformly distributed Co8FeS8, Co2P and Fe2P, and the spherical Rubik's cube-shaped Co8FeS8 is combined and grown together with the nanoflower-shaped Co2P and the nanosheet-shaped Fe2P to form a three-phase heterogeneous structure with rich morphology.
[0029] SEM testing shows that the present invention has the following characteristics: the Fe2P nanosheet structure is directly grown on the NF surface, and then the Co8FeS8 spherical cube structure and the Co2P nanosphere structure are grown on the Fe2P nanosheet structure, and the spherical cube-shaped Co8FeS8 is combined with the spherical Co2P and the flaky Fe2P to form a three-phase heterojunction structure with rich morphology.
[0030] The electrochemical performance test of the present invention shows that: in 1M KOH solution, in the range of 0 to -1.0V, when the current density is 10mA·cm -2 When NF / Co-Fe-S / Co-P / Fe-P has an overpotential of 61-67 mV, and a Tafel slope of 99.51-105.23 mV·dec -1 , after 24h it test, the current retention rate is 98%.
[0031] Therefore, the present invention has the following advantages over the prior art:
[0032] 1. When constructing the NF / CoFeS-CoP-FeP composite catalyst, the synergistic effect is achieved at different active sites and electronic reconstruction interfaces through the synergistic effect of multiple components, so as to improve the catalyst's adsorption capacity for hydrogen atoms and promote the electrochemical hydrogen evolution reaction;
[0033] 2. In the NF / CoFeS-CoP-FeP composite catalyst, the synergistic effect of sulfur and phosphorus can adsorb more thermal neutral electrons / ions, promote the redistribution of electrons, increase the electrochemical active area, and achieve activation when hydrogen ions are adsorbed, that is, activated hydrogen ions are obtained, thereby reducing the energy barrier of the hydrogen evolution reaction and promoting the performance of the hydrogen evolution reaction;
[0034] 3. In the NF / CoFeS-CoP-FeP composite catalyst, a three-phase heterojunction structure is formed between the Co-Fe-S / Co-P / Fe-P loaded on the conductive substrate. The strong coupling effect between the interfaces enhances the bonding force between the materials, greatly reduces the material shedding phenomenon, improves the stability of the catalyst, and prolongs its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the XRD test pattern of Example 1;
[0036] Figure 2 This is a SEM test image of the NF / CoFeS-CoOH-FeOH precursor prepared in Example 1;
[0037] Figure 3 is the linear sweep voltammetry curve of Example 1;
[0038] Figure 4 The Tafel diagrams are Example 1, Comparative Example 1, Reference Example 1, Comparative Example 2, and Comparative Example 3;
[0039] Figure 5 This is the EDS test image of NF / CoFeS-CoP-FeP prepared in Example 1;
[0040] Figure 6 TEM image of NF / CoFeS-CoP-FeP prepared in Example 1;
[0041] Figure 7 This is a SEM test image of NF / CoFeS-CoP-FeP prepared in Example 1;
[0042] Figure 8 This is the IT stability test diagram of Example 1;
[0043] Fig. 9 The XRD test diagrams of Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown;
[0044] Fig.10 This is the SEM test image of NF / CoFeS prepared in Comparative Example 1;
[0045] Fig.11 It is the LSV diagram of comparative example 1, reference example 1, comparative example 2, and comparative example 3;
[0046] Fig.12 This is the SEM test image of pure NF prepared in Reference Example 1;
[0047] Fig.13 This is the SEM test image of NF / CoP prepared in Comparative Example 2;
[0048] Fig.14 This is the SEM test image of NF / FeP prepared in Comparative Example 3. DETAILED DESCRIPTION
[0049] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0050] Example 1
[0051] A method for preparing a NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure comprises the following steps:
[0052] Step 1, preparation of NF / CoFeS-CoOH-FeOH, first, 0.291g of cobalt nitrate hexahydrate, 0.452g of ferric nitrate nonahydrate and 0.304g of thiourea are dissolved in 60mL of deionized water to obtain solution A, and solution A is stirred for 30min, then, under the conditions of hydrothermal temperature of 160°C and hydrothermal time of 5h, a nickel foam NF having a size of 2mm╳3mm is immersed in solution A for hydrothermal reaction, and finally, after washing and drying, a nickel foam simultaneously loaded with cobalt iron sulfide and cobalt iron hydroxide can be obtained, referred to as NF / CoFeS-CoOH-FeOH;
[0053] In the step 1, the NF needs to be washed before immersion, and the washing method is to wash the NF with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence, and after washing, dry it at a drying temperature of 60°C;
[0054] In order to verify the composition of NF / CoFeS-CoOH-FeOH obtained in step 1, XRD test was performed. The test results are shown in Figure 1 As shown, NF / CoFeS-CoOH-FeOH simultaneously has characteristic peaks of Co8FeS8, Co(OH)2 and Fe(OH)2. The test results show that step 1 successfully prepared Co8FeS8, Co(OH)2 and Fe(OH)2.
[0055] In order to verify the microstructure of NF / CoFeS-CoOH-FeOH, SEM test was performed. The test results are shown in Figure 2 As shown in the figure, Co8FeS8, Co(OH)2 and Fe(OH)2 are grown on the NF surface at the same time, among which Co8FeS8 is a spherical Rubik's cube structure, Co(OH)2 is a nanoflower-like structure, and Fe(OH)3 is a nanosheet structure. In addition, the Fe(OH)3 nanosheet structure grows directly on the NF surface, and then the Co8FeS8 spherical Rubik's cube structure and the Co(OH)2 nanoflower-like structure are grown on the Fe(OH)3 nanosheet structure.
[0056] In order to prove the electrochemical performance of NF / CoFeS-CoOH-FeOH, electrochemical performance tests were carried out. The specific method of the electrochemical performance test is to conduct electrochemical performance tests in a three-electrode system consisting of the material to be tested as the working electrode, the mercuric oxide electrode as the reference electrode, the graphite electrode as the counter electrode, and the 1M KOH solution as the electrolyte. The linear sweep voltammetry curve test results are shown in Figure 2. Figure 3 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of NF / CoFeS-CoOH-FeOH is 202 mV;
[0057] The Tafel slope can be calculated by current polarization test. The test results are as follows: Figure 4 As shown in Figure 2, the Tafel slope of NF / CoFeS-CoOH-FeOH is 112.86 mV·dec -1 .
[0058] Step 2, preparation of NF / CoFeS-CoP-FeP, first, 1.0 g of sodium hypophosphite was placed upstream of the tube furnace, and NF / CoFeS-CoOH-FeOH with a size of 2 mm╳3 mm obtained in step 1 was placed downstream of the tube furnace, and then, under an argon atmosphere, the temperature was raised at a rate of 1 °C min -1 The calcination temperature is 300°C and the calcination time is 1 hour. The calcination and phosphating are carried out. After the phosphating is completed, the obtained product is cooled, washed and dried to obtain a foamed nickel simultaneously loaded with cobalt iron sulfide and cobalt iron phosphide, that is, a NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, referred to as NF / CoFeS-CoP-FeP.
[0059] In order to prove the composition of NF / CoFeS-CoP-FeP, XRD test was carried out. The test results are shown in Figure 1As shown, NF / CoFeS-CoP-FeP has characteristic peaks of Co8FeS8, Co2P and Fe2P. The test results show that through the phosphating in step 2, Co(OH)2 and Fe(OH)3 are converted into Co2P and Fe2P respectively, while Co8FeS8 remains unchanged and is in the state of cobalt iron sulfide.
[0060] Since NF / CoFeS-CoP-FeP is composed of three components, it may have a three-phase heterogeneous structure. Therefore, in order to prove that NF / CoFeS-CoP-FeP has a three-phase heterogeneous structure, EDS test and TEM test were carried out.
[0061] EDS test results are as follows Figure 5 As shown, NF / CoFeS-CoP-FeP contains Co, Fe, S and P elements at the same time, but the main distribution areas of S and P elements do not overlap;
[0062] TEM test results are as follows Figure 6 As shown, NF / CoFeS-CoP-FeP has three independent lattice fringes of the three substances, and the boundaries of the regions where the lattice fringes are located are clear, which indicates the existence of a three-phase heterojunction structure. Further specific analysis shows that the lattice fringes with a spacing of 0.2030nm match the (422) crystal plane of Co8FeS8, the lattice fringes with a spacing of 0.2147nm match the (220) crystal plane of Co2P, and the spacing fringes with a spacing of 0.1920nm match the (210) crystal plane of Fe2P, that is, the test results can also prove the successful synthesis of Co8FeS8, Co2P and Fe2P.
[0063] Through the combination of EDS and TEM tests, it can be seen that NF / CoFeS-CoP-FeP has a three-phase heterogeneous structure formed by Co8FeS8, Co2P and Fe2P.
[0064] In order to verify the microstructure of NF / CoFeS-CoP-FeP, SEM test was performed. The test results are shown in Figure 7 As shown in the figure, the basic microstructure of NF / CoFeS-CoP-FeP has no substantial difference from that of NF / CoFeS-CoOH-FeOH, that is, Co8FeS8, Co2P and Fe2P grow on the NF surface at the same time, among which Co8FeS8 maintains a spherical Rubik's cube structure, and when Co(OH)2 is converted to Co2P, the microstructure changes from a nanoflower-like structure to a nanosphere-like structure, and when Fe(OH)3 is converted to Fe2P, the microstructure still maintains a nanosheet structure, but wrinkles appear; the SEM test results also support the conclusion that NF / CoFeS-CoP-FeP has a three-phase heterogeneous structure.
[0065] In order to prove the electrochemical performance of NF / CoFeS-CoP-FeP, electrochemical catalytic performance tests were carried out. The test results are shown in Figure 3 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of NF / CoFeS-CoP-FeP is 61.8mV. Compared with step 1, under the same conditions, the overpotential of NF / CoFeS-CoP-FeP is significantly reduced, indicating that the Co2P and Fe2P generated by phosphating in step 2 can produce a synergistic effect with Co8FeS8;
[0066] The Tafel slope can be calculated by current polarization test. The test results are as follows: Figure 4 As shown, the Tafel slope of NF / CoFeS-CoP-FeP is 99.51 mV·dec -1 Compared with step 1, under the same conditions, the Tafel slope of NF / CoFeS-CoP-FeP decreases, indicating that the three-phase heterostructure formed by step 2 can accelerate the charge transfer rate, that is, increase the reaction rate.
[0067] In order to prove the stability of NF / CoFeS-CoP-FeP, stability performance test was carried out. The test results are as follows Figure 8 As shown, the current density is 10 mA cm -2 , the current retention rate is 98% under the condition of a cycle time of 24h. The test results show that NF / CoFeS-CoP-FeP has good stability.
[0068] In order to prove the role of each component, namely Co8FeS8, Co2P and Fe2P in the technical solution,
[0069] Comparative Example 1 is provided, in which only Co8FeS8 is grown on NF, i.e., NF / Co-Fe-S prepared without introducing Co2P and Fe2P, and the role of Co8FeS8 in the technical solution is demonstrated in combination with Example 1;
[0070] Provide reference example 1 and comparative example 2 and comparative example 3,
[0071] Reference Example 1 is pure NF without any substance loaded as the basic reference example;
[0072] Comparative Example 2 is to grow only Co2P on NF, that is, NF / Co-P prepared without introducing Co8FeS8 and Fe2P, and to demonstrate the role of Co2P in the technical solution in combination with Reference Example 1;
[0073] Comparative Example 3 is to grow only Fe2P on NF, that is, NF / Fe-P prepared without introducing Co8FeS8 and Co2P, and combined with Reference Example 1 to prove the role of Fe2P in the technical solution.
[0074] Comparative Example 1
[0075] A method for preparing NF / CoFeS. Since NF / CoFeS in which only Co8FeS8 grows on NF cannot be obtained by directly adopting the preparation method of step 1 of embodiment 1, in order to obtain NF / CoFeS, it is necessary to increase the amount of thiourea added in step 1 to inhibit the formation of cobalt iron hydroxide, that is, the steps not particularly described in the preparation method are the same as those in embodiment 1, except that: step 2 is not required, and in step 1, the amount of thiourea added is twice that of embodiment 1. The obtained material is referred to as NF / CoFeS.
[0076] The XRD test results of NF / CoFeS are as follows: Fig. 9 As shown, NF / CoFeS only has the characteristic peak of Co8FeS8. The test results show that Co8FeS8 is successfully prepared and the formation of cobalt iron hydroxide is suppressed. The test results can also prove that the composition can be adjusted by adjusting the amount of thiourea added.
[0077] The SEM test results of NF / CoFeS are as follows: Fig.10 As shown, the basic microscopic morphology of Co8FeS8 is not substantially different from that in Example 1, that is, a spherical Rubik's cube structure.
[0078] The electrochemical performance test results of NF / CoFeS are shown in Fig.11 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of NF / CoFeS is 202mV.
[0079] Compared with the NF / CoFeS-CoOH-FeOH obtained in step 1 of Example 1, it can be seen that increasing the amount of S element added to convert all Co and Fe elements into CoFeS has no substantial effect on reducing the overpotential, that is, CoFeOH has no substantial effect on reducing the overpotential.
[0080] Compared with the NF / CoFeS-CoP-FeP obtained in step 2 of Example 1, it can be seen that the introduction of the P element to form CoFeP can improve the electrocatalytic activity and further reduce the reaction overpotential. The reason is that the P element has a high electronegativity and can extract electrons from adjacent transition metal atoms to form negatively charged P atoms, which in turn helps to capture protons. Therefore, the introduction of the P element can increase the adsorption of reaction intermediates on the catalyst surface, increase the electron transfer rate on the catalyst surface, and ultimately achieve the improvement of the electrocatalytic hydrogen evolution performance;
[0081] The Tafel slope test results of NF / CoFeS are as follows: Figure 4 As shown, the Tafel slope of NF / CoFeS is 106.01 mV·dec -1 .
[0082] Compared with the NF / CoFeS-CoOH-FeOH obtained in step 1 of Example 1, it can be seen that increasing the amount of S element added, converting all the Co and Fe elements into CoFeS, the Tafel slope decreases slightly, indicating that the charge transfer capacity becomes lower, that is, CoFeOH has the effect of inhibiting the decrease of the Tafel slope;
[0083] Compared with the NF / CoFeS-CoP-FeP obtained in step 2 of Example 1, it can be seen that the introduction of P element to form CoFeP can accelerate the rate of hydrogen evolution reaction. The reason is that the introduction of P element can increase the active sites of the catalyst, and the synergistic effect of S element and P element will lead to more thermoneutral electron / ion adsorption, electron redistribution, increase the electrochemical active area, and achieve activation when hydrogen ions are adsorbed, that is, activated hydrogen ions are obtained, thereby reducing the energy barrier of the hydrogen evolution reaction and accelerating the rate of the hydrogen evolution reaction.
[0084] Reference Example 1
[0085] A method for preparing pure NF, which does not require the preparation of any load, and therefore does not require the addition of any raw materials, and only requires conventional treatment of the pure NF.
[0086] The SEM test results of pure NF are as follows: Fig.12 As shown, the microscopic morphology of pure NF is smooth without any protruding structures.
[0087] The electrochemical performance test results of pure NF are as follows Fig.11 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of pure NF is 266mV.
[0088] The Tafel slope test results of pure NF are as follows: Figure 4 As shown, the Tafel slope of pure NF is 142.02 mV·dec-1 .
[0089] Comparative Example 2
[0090] A method for preparing NF / CoP. Since only hydroxide needs to be prepared and then phosphated, i.e., no sulfide needs to be prepared, therefore, in the preparation method of step 1 of embodiment 1, thiourea does not need to be added, i.e., the hydroxide can be prepared by a conventional method, i.e., the steps not particularly described in the preparation method are the same as those in embodiment 1, except that: in the step 1, ferric nitrate nonahydrate and thiourea are not added, but ammonium fluoride and urea are added as raw materials by a conventional method, and the mass ratio of ammonium fluoride to urea to cobalt nitrate hexahydrate in step 1 is 4:15:21, and the obtained material is referred to as NF / CoP.
[0091] The XRD test results of NF / CoP are as follows: Fig. 9 As shown in the figure, NF / CoP only has the characteristic peak of Co2P. The test results show that the successful preparation of Co2P means the successful preparation of NF / CoP.
[0092] The SEM test results of NF / CoP are as follows: Fig.13 As shown, a spherical nanosheet structure is grown on the surface of NF. Combined with the reference example 1 and the XRD test results, it can be seen that the spherical nanosheet structure is Co2P. Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, the Co2P obtained by Co(OH)2 conversion has a nano-spherical structure in its microscopic morphology, that is, the microscopic morphology of Co2P can be adjusted by the preparation method of Example 1.
[0093] The electrochemical performance test results of NF / CoP are shown in Fig.11 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of NF / CoP is 117mV.
[0094] Compared with the pure NF obtained in Example 1, it can be seen that the introduction of Co and P elements to form Co2P can reduce the reaction overpotential. The reason is that the electron cloud of the Co atom will be biased towards the P atom under the action of electronegativity. The electronegative P atom can capture positively charged protons, which is beneficial to the adsorption of active hydrogen on the surface of the metal phosphide and the desorption of hydrogen molecules. In addition, the nanosheet Co2P can expose abundant catalytic active sites, thereby achieving high electron transfer and effectively improving the electrocatalytic hydrogen evolution performance.
[0095] Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, it can be seen that the introduction of Fe element to form CoFeP can reduce the reaction overpotential and improve the electrocatalytic hydrogen evolution performance. The reason is that the D band center of the Fe2P adsorption site for the hydrogen adsorption Gibbs free energy is farther away from the Fermi level than Co2P, and the adsorption of hydrogen is weaker, which is more conducive to the analysis of hydrogen, thereby effectively improving the electrocatalytic activity of the catalyst. At the same time, the Co8FeS8 spherical magic cube structure is introduced, so that the originally dispersedly grown spherical Co2P nanosheets are changed into nanospheres and uniformly dispersed and grown on their surface, effectively improving the hydrogen evolution catalytic activity. The reason is that the spherical magic cube-shaped Co8FeS8 provides a large number of active sites for the growth of Co2P nanospheres, reduces the occurrence of agglomeration, and increases the effective contact area between Co2P and the electrolyte.
[0096] The Tafel slope test results of NF / CoP are as follows: Figure 4 As shown, the Tafel slope of NF / CoP is 107.97mV·dec -1 .
[0097] Compared with the pure NF obtained in Example 1, it can be seen that the introduction of Co and P elements to form Co2P can reduce the Tafel slope of the reaction. The reason is that Co2P can redistribute the electrons inside the catalyst, reduce the reaction energy barrier, and facilitate the adsorption and reduction of hydrogen ions, thereby improving the hydrogen evolution efficiency.
[0098] Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, it can be seen that the introduction of Fe element to form CoFeP can significantly reduce the reaction overpotential and improve the electrocatalytic hydrogen evolution performance. The reason is that the binding energy of the density of states of Fe2P is lower than that of Co2P. It can be seen that Fe2P has weaker adsorption of hydrogen and is more conducive to the analysis of hydrogen, thereby effectively improving the electrocatalytic activity of the catalyst. At the same time, the introduction of Co8FeS8 spherical magic cube structure to form a NF / CoFeS-CoP-FeP three-phase heterojunction structure can effectively improve the hydrogen evolution reaction rate. The reason is that the interface coupling effect between CoFeS and CoP and FeS can accelerate the charge transfer rate, further accelerate the process of hydrogen evolution reaction, thereby effectively reducing the Tafel slope of the reaction.
[0099] Comparative Example 3
[0100] A method for preparing NF / FeP. Since only hydroxide needs to be prepared and then phosphated, i.e., no sulfide needs to be prepared, therefore, in the preparation method of step 1 of embodiment 1, thiourea does not need to be added, i.e., the hydroxide can be prepared by conventional methods, i.e., the steps not particularly described in the specific steps are the same as those of embodiment 1, except that: in step 1, cobalt nitrate hexahydrate and thiourea are not added, but ammonium fluoride and urea are added as raw materials by conventional methods, and the mass ratio of ammonium fluoride to urea to ferric nitrate nonahydrate in step 1 is 4:15:32. The obtained material is referred to as NF / FeP.
[0101] The XRD test results of NF / FeP are as follows: Fig. 9 As shown in the figure, NF / FeP only has the characteristic peak of Fe2P. The test results show that the successful preparation of Fe2P means the successful preparation of NF / FeP.
[0102] The SEM test results of NF / FeP are as follows Fig.14 It is shown that a nanosheet structure grows on the surface of NF. Combining the reference example 1 and the XRD test results, it can be seen that the nanosheet structure is Fe2P. Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, the Fe2P obtained by Fe(OH)3 conversion has a wrinkled nanosheet structure, that is, the microstructure of Fe2P can be adjusted by the preparation method of Example 1.
[0103] The electrochemical performance test results of NF / FeP are as follows Fig.11 As shown, in the range of 0 to -1.0 V, at a current density of 10 mA cm -2 When , the overpotential of NF / FeP is 104mV.
[0104] Compared with the pure NF obtained in Reference Example 1, it can be seen that the introduction of Fe and P elements to form Fe2P can reduce the reaction overpotential. The reason is that the metal-rich structure of Fe2P increases the active sites for hydrogen adsorption, accelerates charge transfer, and Fe2P can improve the contact between the catalyst and the electrode, thereby reducing the electron transfer resistance, and ultimately achieving an increase in the hydrogen evolution reaction rate.
[0105] Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, it can be seen that the introduction of the Co element to form CoFeP can significantly reduce the reaction overpotential and improve the electrocatalytic hydrogen evolution performance. The reason is that the multi-component structure shows synergistically enhanced activity at different active sites and electronic reconstruction interfaces, and has excellent electrocatalytic activity compared with the single-component CoP. At the same time, the introduction of the Co8FeS8 spherical cube-shaped structure changes the originally straight Fe2P nanosheets into a wrinkled nanosheet structure, which effectively improves the hydrogen evolution catalytic activity. The reason is that the wrinkled Fe2P nanosheets increase the electrochemically active surface area, thereby expanding the effective contact area between the catalyst and the electrolyte, improving the hydrogen evolution reaction performance, and effectively reducing the hydrogen evolution reaction overpotential.
[0106] The Tafel slope test results of NF / FeP are as follows: Figure 4 As shown, the Tafel slope of NF / FeP is 138.94 mV·dec -1 .
[0107] Compared with the pure NF obtained in Reference Example 1, the introduction of Fe and P elements to form Fe2P can significantly reduce the Tafel slope of the reaction. The reason is that Fe2P can improve the charge transfer ability inside the catalyst, thereby reducing the energy barrier of hydrolysis, and the nanosheet structure of Fe2P can increase the effective contact area with the electrolyte, accelerate the electron transfer rate, and further improve the hydrogen evolution performance of the catalyst.
[0108] Compared with the NF / CoFeS-CoP-FeP obtained in Example 1, it can be seen that the introduction of the Co element to form CoFeP can significantly reduce the reaction overpotential and improve the electrocatalytic hydrogen evolution performance. The reason is that the multi-component structure shows synergistically enhanced activity at different active sites and electronic reconstruction interfaces, and has excellent electrocatalytic activity compared with the single-component FeP. At the same time, the introduction of the Co8FeS8 spherical magic cube structure to form the NF / CoFeS-CoP-FeP three-phase heterojunction structure can effectively improve the hydrogen evolution reaction rate. The reason is that S and P synergistically adsorb more thermoneutral electrons, thereby playing an indirect role in the alkaline HER process, further improving the electrocatalytic hydrogen evolution performance.
[0109] The following conclusions can be drawn from the above Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3:
[0110] Multinary transition metal sulfides have a large number of active sites, which can increase the specific surface area of the composite material on the one hand, and provide growth sites for Co2P and Fe2P on the other hand, so that the phosphide can grow evenly and reduce agglomeration;
[0111] 2. Multi-element transition metal phosphides not only have a metal-rich structure that can increase the active sites for hydrogen adsorption and have good conductivity and chemical stability, but can also regulate the morphology of Co8FeS8 and improve the catalytic performance of hydrogen evolution. Among them, P atoms, as stable proton carriers, can increase the adsorption of reaction intermediates on the catalyst surface and accelerate the transmission rate of electrons on the catalyst surface, ultimately achieving improved electrocatalytic hydrogen evolution performance;
[0112] 3. There is a synergistic effect between S and P elements, which can adsorb thermal neutral electrons / ions, promote the redistribution of electrons, increase the electrochemical active area, and realize activation when adsorbing hydrogen ions, that is, obtaining activated hydrogen ions, thereby reducing the energy barrier of the hydrogen evolution reaction and accelerating the rate of the hydrogen evolution reaction;
[0113] 4. The spherical cube-shaped Co8FeS8 is combined with spherical Co2P and flake Fe2P to form a three-phase heterostructure. The interfacial coupling effect between the three phases can accelerate the charge transfer rate, further accelerate the hydrogen evolution reaction process, and significantly improve the HER performance and stability of the catalyst.
Claims
1. A NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, characterized in that: Using nickel foam as a substrate and a self-supporting skeleton, using cobalt nitrate hexahydrate and ferric nitrate nonahydrate as raw materials and thiourea as a sulfur source, partially sulfided cobalt iron sulfide and cobalt iron hydroxide NF / CoFeS-CoOH-FeOH are grown on the nickel foam through a hydrothermal method, and then using sodium hypophosphite as a phosphorus source, the cobalt iron hydroxide is converted into cobalt iron phosphide through a one-step phosphating method, so that cobalt iron sulfide and cobalt iron phosphide NF / CoFeS-CoP-FeP grown on the nickel foam can be obtained.
2. The NF / CoFeS-CoP-FeP composite material according to claim 1, characterized in that: The microstructure of the Co8FeS8 is a spherical Rubik's cube structure; the microstructure of the Co2P is a spherical nanosheet structure; the microstructure of the Fe2P is a nanosheet structure; and the spherical Rubik's cube-shaped Co8FeS8 and the spherical nanosheet-shaped Co2P are combined together and grown on the Fe2P nanosheets to form a three-phase heterostructure.
3. A method for preparing a NF / CoFeS-CoP-FeP composite material having a three-phase heterogeneous structure, characterized in that The following steps are involved: Step 1, preparation of NF / CoFeS-CoOH-FeOH, first, cobalt nitrate hexahydrate, iron nitrate nonahydrate and thiourea are dissolved in deionized water to obtain solution A, solution A is stirred under certain conditions, then, under certain conditions, nickel foam NF is immersed in solution A for hydrothermal reaction, finally, after washing and drying, nickel foam simultaneously loaded with cobalt iron sulfide and cobalt iron hydroxide can be obtained, referred to as NF / CoFeS-CoOH-FeOH; Step 2, preparation of NF / CoFeS-CoP-FeP, first, sodium hypophosphite is placed upstream of the tubular furnace, and NF / CoFeS-CoOH-FeOH obtained in step 1 is placed downstream of the tubular furnace, and then calcined and phosphated under certain conditions. After the phosphating is completed, the obtained product is cooled, washed and dried to obtain a nickel foam simultaneously loaded with cobalt iron sulfide and cobalt iron phosphide, referred to as NF / CoFeS-CoP-FeP.
4. The preparation method according to claim 3, characterized in that: In the step 1, the mass ratio of cobalt nitrate hexahydrate, ferric nitrate nonahydrate and thiourea is 2:3:2; In the step 2, the mass ratio of sodium hypophosphite to cobalt nitrate hexahydrate in the step 1 is 17:
5.
5. The preparation method according to claim 3, characterized in that: In the step 1, the stirring condition of solution A is that the stirring time is 0.5-1h; In the step 1, the conditions of the hydrothermal reaction are: the hydrothermal temperature is 160° C., and the hydrothermal time is 5 h; In the step 1, the NF needs to be washed before immersion. The washing method is to wash the NF with acetone, hydrochloric acid, deionized water and anhydrous ethanol in sequence. After washing, the NF is dried at a drying temperature of 60°C.
6. The preparation method according to claim 3, characterized in that: In step 2, the calcination and phosphating conditions are: in an argon atmosphere, at a heating rate of 1°C min -1 , the calcination temperature is 300℃, and the calcination time is 1h.
7. A NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, characterized in that: When used as a hydrogen evolution catalyst material, the reaction is carried out in a 1M KOH solution, and the current density is 10 mA cm in the range of 0 to -0.1 V. -2 When NF / CoFeS-CoP-FeP is used, the overpotential is 61-67 mV, and the Tafel slope is 99.51-105.23 mV·dec -1 .
8. A NF / CoFeS-CoP-FeP composite material with a three-phase heterogeneous structure, characterized in that: When used as a hydrogen evolution catalyst material, the reaction is carried out in a 1M KOH solution, and the current density is 10 mA cm in the range of 0 to -0.1 V. -2 When the cycle time is 24h, the current retention rate of NF / CoFeS-CoP-FeP is 98%.
Citation Information
Patent Citations
Non-metallic element S and P doped ferrocobalt hydrotalcite-like catalyst, preparation method and application
CN115212904A
Oxygen-doped ferrocobalt sulfide composite material and preparation method and application thereof
CN116657184A
FeCoS-based active cathode electrocatalyst and preparation method and application thereof
CN117802525A